Implementation of explicit Nordsieck methods with inherent quadratic stability - Bras, Michel; Cardone, Angelamaria; D'Ambrosio, Raffaele (Mathematical Modelling and Analysis, 2013)
The present paper deals with the implementation in a variable-step algorithm of general linear methods in Nordsieck form with inherent quadratic stability and large stability regions constructed recently by Braś and Cardone. Various implementation issues such as rescale strategy, local error estimation, step-changing strategy and starting procedure are discussed. Some numerical experiments are reported, which show the performances of the methods and make comparisons with other existing methods.